Toxicity observed in Some Commercial Detergents Commonly Used in Libya - DR.HASSEN; A.H.BENNASIR; SHANMUGAM SRIDHAR (International Journal of Pharma and Bio Sciences, 2010)
Commercial detergents are available in plenty , and the toxic effects to humans is studied experimentally on an animal and compared for its effects on humans.The study is aimed for the possible toxic effects resulting from the misuse of Lyarkina solution used as a detergent .The inflammatory effect is caused by Lyarkina which is a solution of Sodium hypochlorite with or without sodium hydroxide solution Objective :The possible toxic effects resulting from the misuse of Lyarkina solution used as a substitute for detergents . Experimental set-up : Derna Hospital ,Omar El-Mukthar university ., Derna. Methods : The inflammatory effects of Lyarkina on experimental animals (Rabbits) and on humans is studied .The number of patients on whom the experiment is performed crossed over 100 , and 50% were females . Results : The study revealed that in most patients the inflammation of the skin was evident by severe itching caused by severe irritation and in some patients the eczematic reactions were observed. Even psychological effects were also observed ,where some vegetables ,citrus fruits , garlic and onions influenced the toxicity. Conclusion: The study confirmed the toxic effects to humans on misuse of the Lyarkine solution and should be avoided and replaced by the regular detergents.